2023
DOI: 10.3390/app13116639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Composition of Ancient Glass and Its Identification Based on the Daen-LR, ARIMA-LSTM and MLR Combined Process

Abstract: The glass relics are precious material evidence of the early trade and cultural exchange between the East and the West. To explore the cultural differences and trade development between early China and foreign countries, it is extremely important to classify glass cultural relics. Despite their similar appearances, Chinese glass contains more lead, while foreign glass contains more potassium. In view of this, this paper proposes a joint Daen-LR, ARIMA-LSTM, and MLR machine learning algorithm (JMLA) for the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Moreover, although several studies on the classification of glass types have been reported, for example, Zou et al [16] used one-way analysis of variance to subclassify glass artifacts. Li et al [17] employed a multivariate linear regression model for classifying unknown glass products. Guo et al [18] utilized a support vector machine approach with the sticky slime mold algorithm strategy for classifying glass products.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although several studies on the classification of glass types have been reported, for example, Zou et al [16] used one-way analysis of variance to subclassify glass artifacts. Li et al [17] employed a multivariate linear regression model for classifying unknown glass products. Guo et al [18] utilized a support vector machine approach with the sticky slime mold algorithm strategy for classifying glass products.…”
Section: Introductionmentioning
confidence: 99%